Basic documents in international laws, 2nd edition - Hamid, Abdul Ghafur@Khin Maung Sein (Harun M. Hashim Law Centre, International Islamic University Malaysia, 2007)
The purpose of this book is to provide the students of international law with a convenient collection ofthe textxs that are essential to the study of the subject. The basic documents have been carefully selected and edited in order that they are in conformity with the course outlines of Public International Law 1 (LAW 4610) and Public International Law II (LAW 4611. In this second edition, the book has been completely revised and updated with recent conventions and recent Malaysian statutes.